PENGARUH INTERVENSI MUSIK TRAP TERHADAP PERFORMA BENCH PRESS - Sagesio, Fidro; Hardiarini, Caecilia (Program Studi Pendidikan Musik, 2024)
This study aims to see the effect of trap music intervention on bench press performance. The method used in this research is experimental type research with a crossover design and non-random sampling techniques. The sample was divided into two groups who would do bench press training while listening to trap music and without trap music. Bench press performance is measured in terms of changes in heart rate, upper arm circumference, number of repetitions and total weight that can be lifted. The data obtained were tested using the Shapiro-Wilk normality test and the dependent t test. The research sample consisted of twenty male people with an age range of 18-33 years. The results obtained were the mean difference in heart rate without music compared to music (24.85 ± 8.15) with a P value <0.001. The mean change in weight that can be lifted without music is compared with music (7.25 ± 2.55) with a P value <0.001. The mean change in repetitions without music compared with music (1.05 ± 0.60) with a P value <0.001. The mean change in right upper arm circumference without music was compared with music (0.27 ± 0.24) with a P value <0.001. The results obtained showed an increase in bench press performance in the group with trap music compared to the group without music. Participants who listened to trap music showed an increase in heart rate, upper arm circumference, number of repetitions and total weight lifted.